2048: uma abordagem matemática do jogo e sua aplicação em sala de aula. - Araújo, Renan Lima (2019)
This paper deals with the use of Game 2048 as an educational tool to arouse the interest in Mathematics of EEEP High School students Maria Carmem Vieira Moreira, located in the city of Maracanaú-CE, in order to improve learning and performance. We propose playful approaches to some of the Math content by linking them to the characteristics of the 2048 Game. Because it is an engaging, challenging game that requires a lot of concentration, strategy and reasoning, we have shown through assessments that a group of underperforming students in Math has improved average proficiency and heightened awareness of interest in the subject.